Crop Production, Transport Infrastructure, and Agribusiness Nexus : Evidence from Madagascar - Iimi, Atsushi; You, Liangzhi; Wood-Sichra, Ulrike (World Bank, Washington, DC, 2018)
The literature suggests a wide range of impacts of improved transport connectivity on agricultural growth. Still, the infrastructure-growth nexus remains somewhat mysterious, particularly in the African context, because many rural farmers do not have their own transport means. Using data from Madagascar, the paper reexamines the important roles of agrobusinesses. By applying the spatial autoregressive model, it is shown that proximity to input-oriented agrobusinesses, such as input dealers and equipment suppliers, is particularly important to increase rice production. Fertilizer and irrigation use is also found important, indicating the needs for intensification in rice production. Market accessibility is always found as a significant determinant: transport infrastructure connecting farmers and markets, especially the capital city, Antananarivo, is therefore important to develop and maintain.